2012
DOI: 10.1158/1541-7786.mcr-12-0139
|View full text |Cite
|
Sign up to set email alerts
|

Expression of G Protein-Coupled Receptor 19 in Human Lung Cancer Cells Is Triggered by Entry into S-Phase and Supports G2–M Cell-Cycle Progression

Abstract: It has long been known that G protein-coupled receptors (GPCR) are subject to illegitimate expression in tumor cells. Presumably, hijacking the normal physiologic functions of GPCRs contributes to all biologic capabilities acquired during tumorigenesis. Here, we searched for GPCRs that were expressed in lung cancer: the mRNA encoding orphan G protein-coupled receptor 19 (GPR19) was found frequently overexpressed in tissue samples obtained from patients with small cell lung cancer. Several observations indicate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…A number of genes are involved in cell-cycle processes, such as GPR19 , CDKN2A , USP11 and MX2 . GPR19 encodes for a G protein-coupled receptor and is reported to be associated with lung cancer and melanoma22. It is suggested that G protein-coupled receptors are the most “druggable” family of proteins23.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes are involved in cell-cycle processes, such as GPR19 , CDKN2A , USP11 and MX2 . GPR19 encodes for a G protein-coupled receptor and is reported to be associated with lung cancer and melanoma22. It is suggested that G protein-coupled receptors are the most “druggable” family of proteins23.…”
Section: Discussionmentioning
confidence: 99%
“…); moreover, expression of GPR19 in lung cancer cells is triggered by entry into S‐phase and in this case seems to promote progression from G2 to M phase (Kastner et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting not least because the situation appears to be different for some other GPCRs that exhibit cell-cycle dependent regulation of expression. For example the chemokine receptor CXCR3 is expressed in both S and G2-M phases in human microvascular endothelial cells (Romagnani et al 2001); moreover, expression of GPR19 in lung cancer cells is triggered by entry into S-phase and in this case seems to promote progression from G2 to M phase (Kastner et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression profiling in Kastner et al's work was used in our study [13], which includes 8 SCLC, 16 NSCLC, and 14 normal lung tissue samples. It was retrieved from NCBI Gene Expression Omnibus (GEO) (Accession number: GSE40275).…”
Section: Methodsmentioning
confidence: 99%